Introduction to fluid mechanics - Shaughnessy, Edward J., Jr (Oxford University Press, 2005)
"Introduction to Fluid Mechanics provides a balanced and uniquely visual treatment of the tools used in solving modern fluid mechanics problems. Presenting an image-intensive approach to fluid dynamics through classic kinematic concepts, the book demonstrates the importance of flow visualization in a framework of modern experimental techniques and flow simulation. Detailed photographs and diagrams of fluid motions and phenomena throughout the text help students to see and understand why equations change drastically for different types of flows. Output illustrations from CFD (computational fluid dynamics) programs illustrate the possibilities of flow behavior, enabling students to concentrate on ideas instead of mathematics. The book also provides the means to solve interesting problems early in the course by presenting case studies at the beginning of the text. These cases are revisited later to reinforce empirical rules and help explain advanced methods of analyzing a flow. Creating a foundation for further study in this important and exciting field, Introduction to Fluid Mechanics is ideal for a first course in fluid mechanics. The book is designed to accommodate students concentrating in mechanical engineering as well as those in the civil, aerospace, and chemical engineering fields."--Publisher's description